The Correlation between Waiting Time and Patient Satisfaction in the Outpatient Unit at the Gateway Sehat Hospital, Mahulu Ujoh Says - Apriliana Katarina; Edi Sukamto; Abd Kadir (Formosa Journal of Science and Technology, 2023)
This type of quantitative research uses descriptive analytic methods with a cross sectional approach. In this study, researchers wanted to know the relationship between waiting time and patient satisfaction in the outpatient unit at the Gateway Sehat Mahulu Ujoh Bilang Hospital in 2023. The sampling technique used non-probability sampling with the accidental sampling technique, which is a sampling technique based on chance, so that researchers can sample anyone they meet without prior planning. The population in this study were patients who visited the outpatient unit at the Gateway Pratama Hospital, Mahulu Ujoh Bilang, with a total of 213 respondents. The results of the Chi Square statistical test for the SPSS 25 program in table 4.8 obtained a P-value < α where the P-value (0.000) < α (0.05) so that it can be concluded that there is a significant relationship between waiting time and patient satisfaction in the outpatient unit at the Gateway Sehat Mahulu Ujoh Bilang Hospital in 2023. There is a significant relationship between waiting time and patient satisfaction in the outpatient unit at the Gateway Sehat Mahulu Ujoh Bilang Hospital in 2023.